UPPER LAYER CIRCULATION IN THE BANDA SEA IN RESPONSE TO THE ONSET OF MONSOON WINDS - Hutahean, W.; Wilson, R. E. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1992)
Aspects of the upper layer circulation in the interior of the Banda Sea, Indonesia, associated with local forcing by monsoon winds are examined numerically through the use of a reduced gravity model. The basin is located between approximately 4°S and 8°S and is partially enclosed by chains of islands. The primary emphasis is an evaluation of the free wave response which contributes to the steady or slowly varying circulation. Basin response appears to be characterized by interacting Kelvin waves and Rossby at low frequencies, and by evanescent Poincare waves of higher frequencies. Passages between islands along the perimeter of the basin appear to be nearly, impermeable to Rossby waves, which contribute to a pattern of westward propagating quasi geostrophic eddies. This pattern would persist during periods of wind transition.